DIFFERENCES IN THE REACTIVE FORCE OF ELITE AND SUB-ELITE SPRINTERS - Milan Čoh; Milan Žvan; Stojan Burnik (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The study aimed at establishing the differences between the kinematic and dynamic parameters of reactive force which is one of the most important biomotor ability of sprinters. Reactive force was assessed during a drop jump from 45 cm. The basic kinematic and dynamic parameters were registered using the Smart 600E bipedal force platform which had been synchronised with a 3D infra-red kinematic system. The sample of subjects consisted of 12 elite sprinters. Based on the analysis of variance (Anova) the main generators of reactive force which differentiate between elite and sub-elite sprinters were established. The statistically significant differences between the sprinters were found in the following: jump height, eccentric phase time, take-off velocity, eccentric velocity and force impulse in the eccentric phase.